Presenting in International Conference: An Interview Study on the Students’ Public Speaking Anxiety - Rahmah, Seftiannur; Farhan, Miftah Al; Aflahah, Noor Aida; Nadia, Hafizhatu (Jurnal Keilmuan dan Keislaman, 2023)
This study aims to find out about the experiences of English students who have attended an International conference and how they can control their anxiety when they are going to present at an International conference. The research approach used is qualitative. This research took place at one of the universities in Banjarmasin. This research involved students and alumni majoring in English education to find out their experiences who have presented at the International Conference. This study uses an interview instrument to find out more about the data to be collected from all participants. The results of the interview confirmed that all participants were invited by the lecturer and asked to present papers that had been written into an article. All participants brought different topics according to the lecturer who invited them. There were several participants who attended the International Conference online, and some were offline during presentations at the International Conference. There were several participants felt very anxious, just worried, and there were even participants who said they were not worried. The results of interviews showed that they controlled anxiety before the presentation by practicing continuously, reading a lot of literature, being prepared, reading key points, and believing in themselves.